Analisis Dampak Perceraian Orang Tua terhadap Tindakan dan Optimisme Remaja di Desa Pematang Asilom - Adam Adhitya Perdana; Misrah Misrah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Parental divorce is one of the family events that can influence adolescents' psychological development and behavior, including the way they perceive their future. This study aims to analyze the impact of parental divorce on adolescents' behavior and optimism, as well as to identify the factors that shape adolescents' optimism in Pematang Asilom Village. This research employed a qualitative approach using a case study method. Data were collected through in-depth interviews with six adolescents from divorced families, as well as observations and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing. The findings indicate that parental divorce affects adolescents' behavior through emotional distress, decreased learning motivation, changes in social interactions, and increased responsibility among some adolescents. The impact on optimism is not uniform, as it depends on each individual's adaptation process. Adolescents' optimism is shaped by family support, social support, the ability to derive meaning from life experiences (meaning-making), and future orientation. This study proposes a conceptual model demonstrating that optimism develops through an adaptation process supported by these protective factors. The findings underscore the importance of strengthening family and social support systems to help adolescents maintain hope and build a positive future after experiencing parental divorce.